Sosialisasi Perawatan dan Pencegahan Diabetes Mellitus pada Lansia - Wahyu; Jumain (Yayasan Kawanad, 2022)
Patients with diabetes mellitus have increased from year to year. Patients with diabetes mellitus are prone to injury, are prone to relapse, and also many other risks that may be faced by people with diabetes mellitus. As long as people with diabetes mellitus are at home, they cannot be directly supervised by nurses, unlike when they are in the hospital. So it needs to be conveyed to patients and their families how to modify the environment to maintain blood sugar stability and keep diabetes mellitus patients from developing diabetes wounds. The purpose of implementing community nursing concepts and theories that have been obtained at the academic stage is actually in providing community nursing care to the elderly at the Pelita Hati Panti Foundation in Loru village, Sigi Biromaru sub-district, Sigi district. The method used is the strategy of conducting health education for diabetes mellitus. Based on the results of Diabetes Mellitus Health counseling and exercise for the elderly in Loru village, Biromaru District, Sigi Regency, the conclusions in this counseling are: From the results of the health counseling, some patients have less knowledge about diabetes mellitus. The results of the counseling showed that there was significant progress by the elderly after counseling in terms of knowledge about diabetes mellitus. With the results of this health education, it is hoped that it can provide information for the elderly, especially people with Diabetes Mellitus to better understand so that blood sugar levels are controlled.